Pain Scores and Return to Activities/Sport Following Dehydrated Micronized Allogenic Cartilage and Isolated Microfracture for Treatment of Talar Osteochondral Lesions. Issue 4 (22nd October 2020) - Lau, Brian; Johnson, Brianna; Oji, David E.; Chou, Loretta B.
Category: Sports Introduction/Purpose: Osteochondral lesions of the talus (OLT) are common injuries, however management remains challenging. Lesion size remains a common determinant of treatment and microfracture remains common for smaller lesions. Microfracture provides access to mesenchymal stem cells within the subchondral bone. Dehydrated micronized allogenic cartilage (DMAC) (BioCartilage, Arthrex, Naples, FL) utilizes a single stage attempt to augment microfracture with a scaffold over the defect to improve hyaline cartilage restoration. DMAC requires hydration with plasma rich protein (PRP) or bone marrow aspirate concentrate (BMAC). Currently, there is limited literature on pain scores and return-to-activities and satisfactory return- to-sport following DMAC treatments. The purpose of this study is to report pain scores, percent and time return-to -activities, percent and time to satisfactory return-to-sport following microfracture + DMAC and isolated microfracture. Methods: We reviewed a series of 65 cases (37 female and 28 male; mean age 34.6 (SD 14.1); mean BMI 27.3 (SD 6.2)) between 2010 and 2019 in which surgical treatment for OLT consisted of microfracture + DMAC, or isolated microfracture. Surgical procedure was determined by treating surgeon. Demographic, visual analog scale (VAS) pain scores (0-10), return-to-activities, and satisfactory-return-to-sport were collected preoperatively and postoperatively at 3-months, 6-months, and 1 year. Return-to- activities was defined as any engagement in desired activities, whereas satisfactory-return-to-sport was determined by patient- report. T-tests were used to determine between group differences. Results: Sixty-five cases (DMAC 25; isolated-microfracture: 40) demonstrated mean pain score at 3-months for DMAC and isolated-microfracture of 0.8 and 2.0, respectively, (p=0.04). There were no significant differences in remaining pain scores. By 1- year, 100% of DMAC and 87.5% of isolated-microfracture returned-to-activities, p=0.09. Of those that returned-to-activities there was no difference in time-to-return-to-activities between groups 82.9 days vs 82.4 days. By 1-year, patients that return-to-sport demonstrated a patient-reported satisfactory-level-of-return of 52.0% in DMAC and 37.5% in isolated-microfracture. Of those that returned satisfactorily-to-sport, the time-to-satisfactory-return-to-sport was similar (mean 139.5 and 135.7 days, p=0.66). A subgroup analysis of microfracture + DMAC group determined that PRP (n=16) had less pain at 3 months than BMAC (n=9), mean 0.8 vs 2.0, respectively; p=0.03, with no other differences noted (p>0.05). Conclusion: The use of microfracture + DMAC may improve early post-operative pain scores and improve ability to return to a patient-reported satisfactory level of sport by 1-year. Isolated microfracture and DMAC augmentation had similar rates and times to return-to-activities, and pain levels after 6-months post-operatively. The use of PRP to supplement DMAC improved early post- operative pain scores compared to BMAC which may be related to donor-site morbidity. Otherwise PRP and BMAC supplementation of DMAC had similar subsequent pain scores, and rate and time to return to activities. Augmentation of microfracture with DMAC for OLTs may improve outcomes compared to microfracture alone.